Twelve-Month Retention in and Impact of Enhance®Fitness on Older Adults in Hawai‘i - Michiyo Tomioka; Kathryn L. Braun; Yan Yan Wu; Kay Holt; Paula Keele; Lori Tsuhako; Johnny Yago (Journal of Aging Research)
Introduction. Enhance®Fitness is a low-cost group exercise program designed specifically for older adults (60+ years) to improve physical performance. The Hawai‘i Healthy Aging Partnership, a statewide health promotion initiative, has continuously offered Enhance®Fitness to Hawai‘i’s multicultural population since 2007. This study examined 12-month participation in and impact of Enhance®Fitness on physical performance among older adults in Hawai‘i. Method. Linear mixed-effects models were applied to analyze the physical performance measures (chair-stands, arm curls, and the up-and-go test) collected at baseline (month 0) and at 4, 8, and 12 months. We also compared the characteristics of participants who participated in the program for 12 months with those who dropped out in order to gain insights on participant retention. Results. Of 1,202 older adults with baseline data, 427 (35.5%) were continuously enrolled in Enhance®Fitness for 12 months and participated in follow-up data collection. On average, participants attended 63.7% of thrice-weekly classes each month. Participants’ physical performance measures improved after 4 months, continued to improve until 8 months, and were maintained thereafter. Besides continuous attendance, performance-measure improvements were associated with younger age, male gender, living with others (vs. alone), and fewer chronic conditions. Compared to those who completed 12 months of the program, the 775 who left the program over the course of the year were more likely to be younger, to be Caucasian (vs. Asian or Pacific Islander), to self-report depression as a chronic condition, and to have lower levels of fitness at baseline. Common reasons for dropping out were illness, relocation, time conflicts, lost interest, and transportation issues. Conclusions. Long-term participants in Enhance®Fitness initially improved and then maintained physical performance. Future research is needed to identify strategies to maintain enrollment of older adults in the exercise programs over time.